Six, not two, species of Acisoma pintail dragonfly (Odonata: Libellulidae) - Mens, Lotte P.; Schütte, Kai; Stokvis, Frank R.; Dijkstra, Klaas-Douwe B. (Zootaxa, 2016)
The dragonfly genus Acisoma is revised based on adult male morphology and COI sequence data. Six species are recognised, including the new species A. attenboroughi sp. nov. Diagnoses and a key to males of all species and illustrations of all relevant characters are provided. A. inflatum, A. variegatum and A. trifidum are confined to continental Africa, while A. panorpoides is restricted to Asia. A. ascalaphoides is known only from threatened littoral forest fragments on the east coast of Madagascar, while A. attenboroughi is widespread across the island. The new species honours Sir David Attenborough on his 90th birthday.